Dopaminergic Receptors on CD4+ T Naive and Memory Lymphocytes Correlate with Motor Impairment in Patients with Parkinson’s Disease - Kustrimovic, Natasa; Rasini, Emanuela; Legnaro, Massimiliano; Bombelli, Raffaella; Aleksic, Iva; Blandini, Fabio; Comi, Cristoforo; Mauri, Marco; Minafra, Brigida; Riboldazzi, Giulio; Sanchez-Guajardo, Vanesa; Marino, Franca; et al. (Scientific reports, 2016)
Parkinson’s disease (PD) is characterized by loss of dopaminergic neurons in substantia nigra pars compacta, α-synuclein (α-syn)-rich intraneuronal inclusions (Lewy bodies), and microglial activation. Emerging evidence suggests that CD4+ T lymphocytes contribute to neuroinflammation in PD. Since the mainstay of PD treatment is dopaminergic substitution therapy and dopamine is an established transmitter connecting nervous and immune systems, we examined CD4+ T naive and memory lymphocytes in PD patients and in healthy subjects (HS), with specific regard to dopaminergic receptor (DR) expression. In addition, the in vitro effects of α-syn were assessed on CD4+ T naive and memory cells. Results showed extensive association between DR expression in T lymphocytes and motor dysfunction, as assessed by UPDRS Part III score. In total and CD4+ T naive cells expression of D 1 -like DR decrease, while in T memory cells D 2 -like DR increase with increasing score. In vitro , α-syn increased CD4+ T memory cells, possibly to a different extent in PD patients and in HS, and affected DR expression with cell subset-specific patterns. The present results support the involvement of peripheral adaptive immunity in PD, and may contribute to develop novel immunotherapies for PD, as well as to better use of current dopaminergic antiparkinson drugs.